Expressive silence: managing message through sign language on Tiktok by deaf communicators - Setyaningsih, Santi; Utari, Prahastiwi; Satyawan, Ignatius Agung (Penerbit Universiti Kebangsaan Malaysia, 2024)
Social media has emerged as a powerful tool for fostering inclusivity, enabling people with disabilities to convey diverse messages to broad audiences. The TikTok account @jennifernatalie_ exemplifies this by delivering educational content on sign language. As a deaf Social Media Influencer (SMI), @jennifernatalie_ has successfully engaged her followers despite communication challenges. This research aims to analyze the communication strategies employed by @jennifernatalie_ in promoting sign language education on TikTok. Using a qualitative content analysis approach, the study examined 112 short videos from the Sign Language playlist on @jennifernatalie_’s TikTok, supplemented by relevant literature. The findings reveal that @jennifernatalie_ employs specific strategies to effectively deliver sign language education. These include using TikTok’s features, such as closed captions, to enhance accessibility and involving her child as a co-communicator, which adds relatability and diversity to the content. Her messaging targets both disabled and non-disabled audiences, extending her reach and impact. Additionally, she utilizes other platforms like Instagram and YouTube to support her educational efforts. The study highlights @jennifernatalie_’s ability to bridge communication gaps through social media, demonstrating how influencers can educate and raise awareness on important issues. This suggests a model for other educators and influencers to emulate in their efforts to promote inclusivity and accessibility.